PREGNANCY OUTCOMES IN TURNER SYNDROME - Borges, Maria de Fátima; Trovó de Marqui, Alessandra Bernadete (Acta Biologica Brasiliensia, 2025)
Turner Syndrome (TS) is a genetic condition characterized by partial or complete deletion of the X sexual chromosome and it can be present as a monosomy (45,X), mosaicism with two or three different cellular lines (45,X/46,XX; 45,X/47,XXX; 45,X/46,XX/47,XXX) or structural abnormality [46,X,i(Xq); 46,X,r(X); 46,X,del(X)]. TS is tightly associated with hypergonadotropic hypogonadism and ovarian dysgenesis, typically resulting in infertility in the great majority of patient. This manuscript addresses the fertility, pregnancy and motherhood in women with TS. In general, TS patients experience adverse pregnancy associated outcomes and this last is considered high risk. This way, the management of pregnancy in TS with a multidisciplinary team, composed mainly by maternal–fetal medicine specialists and cardiologists, should be implemented in order to reduce complications for mothers and infants.